DASHBOARD SISTEM INFORMASI OPERASIONAL PT TELKOMSEL CABANG DEMANG LEBAR DAUN PALEMBANG - Ade Putra (Jurnal Ilmiah Matrik, 2016)
This research was done to make the Dashboard System Operational Information Office PT Telkomsel Branch demang Lebar Daun Palembang using PHP and Mysql. In this research Dashboard System Operational Information Office can manage the data generated work routines include vehicle data, vehicle operational data, telephone data, the data usage of telephone, electrical data and electricity usage data in the PT. Telkomsel Branch demat Lebar Daun Palembang. Office Operational Information System Dashboard is made also to support the bookkeeping of the cost which is issued by the office of PT. Telkomsel Palembang Branch demang Lebar Daun in the form of reports that the operational facility at the office of PT. Telkomsel Branch demang Lebar Daun Palembang. In the development of the Office of Operations Information System Dashboard using waterfall development method comprising the steps of planning, analysis, design, implementation and testing.